Hubungan Dukungan Sosial dan Beban Kerja Mental dengan Burnout Syndrome Pekerja PT Trans Marga Jateng - Ardiningrum, Nur Annisa; Atmojo, Tutug Bolet; Wijayanti, Reni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
Burnout syndrome is a condition of physical, mental and emotional exhaustion due to stress that results from long-term involvement in emotionally demanding situations. In Indonesia, 83% of health workers experience moderate and severe burnout syndrome. Factors that cause burnout syndrome that have a strong and consistent relationship are social support and workload. This study aims to determine the relationship between social support and mental workload with burnout syndrome. This research is an analytical observational study, with a cross sectional design. Respondents were taken from PT Trans Marga Jateng toll road operational workers, with 85 respondents from a total of 230 workers using a purposive sampling technique. This study uses a validated questionnaire to measure burnout syndrome, social support, and mental workload of workers. The data analysis technique used are somers'd correlation test and ordinal logistic regression test. The results showed that the majority of respondents experienced moderate category of burnout syndrome, good category of social support, and moderate category of mental workload. The results of the somers'd correlation test showed that there was a significant relationship between burnout syndrome and social support (p = 0.001) with the negative correlation direction and weak correlation strength (r = -0.354), and there was a significant relationship between burnout syndrome and mental workload (p = 0.000) with a positive correlation and moderate correlation strength (r = 0.506). The results of the ordinal logistic regression test show that the mental workload variable has a stronger influence on burnout syndrome than the social support variable.